Learning environments in English classrooms in Singapore: determinants and effects - Lim, Ching-Tse Donna (Curtin University, 2013)
This study investigated the learning environment and attitudes among approximately 400 Primary 6 children in Singapore. A modified learning environment and attitude questionnaire, based on the What Is Happening In this Class? (WIHIC), Test of Science Related Attitudes (TOSRA) and Morgan-Jinks Student Efficacy Scale (MJSES), was validated. Sex and ethnic differences were found in learning environment perceptions and attitudes. Associations emerged between students’ attitudes and the classroom learning environment, which replicates past research